A Prospective Study of Asymptomatic Bacteriuria in Sexually Active Young Women - Hooton, Thomas M; Scholes, Delia; Stapleton, Ann E; Roberts, Pacita L; Winter, Carol; Gupta, Kalpana; Samadpour, Mansour; Stamm, Walter E (The New England journal of medicine, 2000)
Quantitative analysis of bacteria in urine cultures was developed several decades ago 1 – 4 to establish reliable criteria for discriminating between infection and contamination in asymptomatic subjects, with the expectation that asymptomatic infection might be associated with pyelonephritis, hypertension, renal disease, and complications of pregnancy. 5 – 8 In studies of asymptomatic bacteriuria, counts of at least 10 5 colony-forming units per milliliter usually predicted persistently high levels of bacteriuria, whereas counts of less than 10 5 colony-forming units per milliliter usually meant persistently low levels of bacteriuria, with distinctive microflora for each group. 2 , 4 , 5 Moreover, high concentrations of pathogenic bacteria in serial voided . . .